Funds Management as Relation System in Business Company for Highly Effective Finance Administration - Golovanova, Natalia B.; Asyaeva, Elmira A.; Gavrilenko, Sofia A.; Temirkanova, Alla V.; Sokolov, Alexandr A. (International Journal of Economics and Financial Issues, 2016)
Particularly relevant in a period of increasing competition in all sectors of the economy, where the major indexes falling rapidly, is cost management in enterprises of different types. At the moment, there is a period of rapid growth of the completion of the majority of companies, and the transition in the process of mergers and acquisitions. The productivity of domestic branded business - processes rapidly is of paramount importance not only for the efficient operation, as well as to maintain its place in the market. The stumbling block in achieving operational efficiency of any enterprise is the existence of an effectively functioning system of the enterprise. Also note that the fundamental nature of the competitive position of the company in today’s market is characterized by high efficiency of its financial management system of the company. financial management system is a set of tools with which the company’s management can rapidly generate accurate information about every aspect of the company. As well as to monitor for compliance with its performance tactical objectives and strategic plans, moreover, fully analyze the problems that arise in the operation of various types of enterprises, and to seek the best options for their solutions. Keywords: financial administration, financial management, budgeting, transaction, financial resources, financial leverage JEL Classifications: G02, G3, G32